EFFECT OF FIRM SOLVENCY ON FINANCIAL PERFORMANCE OF ICT FIRMS LISTED ON THE NIGERIAN EXCHANGE GROUP (Journal of Global Accounting, 2023)
The study ascertained the effect of firm solvency on the financial performance of listed Information and Communication Technology firms in Nigeria. The specific objective of the study was to examine the extent to which debt ratio affects return on asset, return on equity and earnings per share of quoted Information and Communication Technology firms in Nigeria. This study deployed ex-post facto research design. Seven firms were selected from a population of nine Information and Communication Technology (ICT) firms on the Nigerian Exchange Group. The study focused on the collected data from the financial statements or annual reports  of the selected listed ICT firms in Nigeria for the period of six (6) years from 2015 to 2020. Ordinary Least Square regression was used to test the hypothesis which revealed that: firm solvency does not significantly affect Return on Asset of listed ICT firms on the Nigerian Exchange Group (F = 0.14, Prob>F= 0.8657); firm solvency does not significantly affect return on equity of listed ICT firms on the Nigerian Exchange Group (F = 2.50, Prob>F= 0.0954); firm solvency significantly affects Earnings Per Share of listed ICT firms on the Nigerian Exchange Group (F = 4.81, Prob>F= 0.0136). It was recommended that the management of ICT firms should ensure their debt structure is optimum with a view to avoid being cash trapped and debt ridden.
Keywords: Corporate Performance; Firm Solvency; Information and Communication Technology